(3OhMI GdCfhGQ aj PcQ GdaQjO ef GdCTYGQs - (3eMeO Hf eMeO Hf Rjf GdOjf GdMSjfj GdSjO LhGO GdSjGg HhT, GdSjO LhGO GdSjGg HhT,J (B1247 (3g` s
(3ChdgG (B:s
(3CeG HYO(B: (3ajbhd CdJeSfj HYV NdGfj ef ENhGf GdUaG Cf COhf dg eLehYI JMJhj aj GdZGdH Ydi fXe COHGA gPG GdReGf ef GdeYGUQjf s
(3BNQgG (B:s
(3hGTaY HBdg ef bO RchG fSHG Hg hCUMGHg Chai GdhQi MSHG hQfM Gdchf ef CeOGMge WQHG aGQfMJ YPHGJ GdHGf QjM UHG s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B11 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdCOHs